Initial Initiative to Explore the Potential of Special Interest Tourism Health and Wellness Tourism in the Ecotourism Area of ​​Terbah Village, Gunungkidul Regency - Putri Rahmadyani Condroasih; Arma Zalfa Nadifah; Muhamad (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Kalurahan Terbah is a village area with diverse and pristine natural landscapes. One of the potential tourist destinations is Selotumpang Cave. The environmental appeal and natural resources in this area have the potential to be developed into an ecotourism area. The Health and Wellness Tourism special interest tourism which is currently trending in the community is one of the potential types of tourism that underlies the design of the development of the potential for Health and Wellness Tourism special interest tourism in Kalurahan Terbah, with the main focus on the forest bathing tourism development plan. Data collection activities were carried out by the Community Empowerment Learning Community Service Lecture (KKN-PPM) team of Gadjah Mada University (UGM) unit YO-081 in Pudak Hamlet, Kalurahan Terbah from April to May 2024. The methods used consisted of literature studies, interviews, observations, and dissemination to Kalurahan Terbah. The results of data collection include a study of the ecotourism potential of Kalurahan Terbah which includes the landscape of Kalurahan Terbah and a map of regional potential. The data collection process also produced a Health and Wellness Tourism development plan which was then compiled in the form of a paper to be disseminated to Kalurahan Terbah. Through the dissemination program carried out, Kalurahan Terbah received recommendations that can be used as considerations for making policies related to the management of tourism potential in the future. Based on the analysis that has been carried out, Kalurahan Terbah has the potential and natural attractions that are beautiful, so developing tourism potential in Kalurahan Terbah is expected to improve the community's economy in the future. The suggestions given include the formation of a Health and Welfare Tourism Awareness Group (Pokdarwis), training for Micro, Small, and Medium Enterprises (UMKM) and community groups, preparation of tourism product diversification through BUMKal Giri Puspita drinking water products, and the creation of supporting tourism facilities to realize Healthy and Welfare Tourism in Kalurahan Terbah.